2013
DOI: 10.1063/1.4775589
|View full text |Cite
|
Sign up to set email alerts
|

Different structures give similar vibrational spectra: The case of OH− in aqueous solution

Abstract: We have calculated the anharmonic OH(-)(aq) vibrational spectrum in aqueous solution with a "classical Monte Carlo simulation + QM/MM + vibrational" sequential approach. A new interaction model was used in the Monte Carlo simulations: a modified version of the charged-ring hydroxide-water model from the literature. This spectrum is compared with experiment and with a spectrum based on CPMD-generated structures, and the hydration structures and H-bonding for the two models are compared. We find that: (i) the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…As can be seen from the comparison of the OH À (H 2 O) n versus the bare OH À (also see Table S1, ESI †), all methods show blue shifting when OH À is hydrated and this has been examined in detail by Hermansson and coworkers. 30,31,54,55 However a more drastic change is seen in the large decrease in the intensity with increasing n for OH À (H 2 O) n . In particular, at n = 3 the intensity becomes two orders smaller than the bare OH À .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen from the comparison of the OH À (H 2 O) n versus the bare OH À (also see Table S1, ESI †), all methods show blue shifting when OH À is hydrated and this has been examined in detail by Hermansson and coworkers. 30,31,54,55 However a more drastic change is seen in the large decrease in the intensity with increasing n for OH À (H 2 O) n . In particular, at n = 3 the intensity becomes two orders smaller than the bare OH À .…”
Section: Resultsmentioning
confidence: 99%
“…However recent studies by Hermansson and coworkers showed that such a water molecule exists mainly due to the water network and not due to the direct interaction with hydroxide. 30,31 Thereby, we believe that the gas phase model given in Fig. 1 is a good zeroth order picture to provide a qualitative understanding of the electronic and vibrational states of hydroxide in the aqueous phase.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…For Al 3+ cation, the potential parameters from [10] were used, while the hydroxide ions were modeled by the so-called "simple-charge" potential parameters described in details in [18].…”
Section: Statistical Mechanics Simulationsmentioning
confidence: 99%
“…This investigation is also motivated by an interest in establishing connections between proton transfer dynamics in aqueous hydroxide and recent two-dimensional infrared spectroscopy (2DIR) of the participating O–H stretching vibrations. , Considerable evidence indicates that the solvent electric field exerted along an O–H bond in neat water determines the O–H stretch vibrational frequency, and thereby the shape of the proton potential. It is therefore likely that the same collective variables that influence the proton transfer dynamics also describe the IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%